The Pragmatics of Sībawayhi’s Book in the Studies of the Arabists - Gedamy, Abdelmonem; Al-Horais, Nasser (Dirasat: Human and Social Sciences, 2026)
Objectives: This paper aims to present and analyze a selection of studies by a group of Arabists published in Europe, utilizing modern pragmatic theory as analytical tools to approach works of Sībawayhi in this regard. Methods: The paper seeks to uncover the underlying philosophy of these studies and analyze their outcomes within a critical analytical framework. Results: One of the significant findings, through examining pragmatic analyses by Arabists of Sībawayhi’s work, is their view of the Arabic linguistic tradition represents a crucial chapter in the history of global linguistic thought. Modern linguistics proves essential in understanding many aspects of Arabic tradition. From Arabists’ approaches to Sībawayhi’s work, it becomes evident that Sībawayhi possessed concepts and analyses that reflect his awareness of context importance in linguistic analysis. For example, in Carter’s approach, he draws parallels between Sībawayh’s concepts and Gricean pragmatics, highlighting that, according to Sībawayhi, speaker is not only participant in a cooperative activity with a receiver in a realistic context; rather, the context itself can become an active component in grammatical structure of speech, which contributes to language learning and teaching in real-life usage and situations. Conclusions: These studies underscore originality of Sībawayhi’s linguistic contributions, which are not only groundbreaking in field of Arabic linguistics but also span entire history of linguistics up to modern era. This is reflected in the pragmatics of Sībawayhi’s analyses and comparisons between his concepts and those of Grice and Leech’s integrative framework.